2003
DOI: 10.1152/ajpgi.00545.2002
|View full text |Cite
|
Sign up to set email alerts
|

Role of nitric oxide in β3-adrenoceptor activation on basal tone of internal anal sphincter

Abstract: Banwait, Kuldip S. and Satish Rattan. Role of nitric oxide in ␤3-adrenoceptor activation on basal tone of internal anal sphincter. Am J Physiol Gastrointest Liver Physiol 285: G547-G555, 2003. First published May 7, 2003 10.1152/ ajpgi.00545.2002.-Effects of activation of ␤3-adrenoceptor (␤3-AR) have not been determined in the spontaneously tonic smooth muscle of the internal anal sphincter (IAS). The effects of disodium (R,R)-5-[2-[2-3-chlorophenyl)-2-hydroxyethyl]-amino]propyl]-1,3-benzodioxole-2,2-dicarbox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 39 publications
2
14
0
Order By: Relevance
“…41 It has also been suggested that I/R upregulates iNOS expression, and that inhibition of iNOS improves contractile function and blood flow. 42 However, other studies have shown that induction of iNOS, by prior administration of monophosphoryl lipid A, conferred myocardial protection against I/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…41 It has also been suggested that I/R upregulates iNOS expression, and that inhibition of iNOS improves contractile function and blood flow. 42 However, other studies have shown that induction of iNOS, by prior administration of monophosphoryl lipid A, conferred myocardial protection against I/R injury.…”
Section: Discussionmentioning
confidence: 99%
“…The procedure to describe details of tissue preparation and isometric tension recording in the IAS smooth muscle has been published in a number of our earlier publications (Moummi and Rattan, 1988;Banwait and Rattan, 2003;Rathi et al, 2003;Sarma et al, 2003).…”
Section: Methodsmentioning
confidence: 99%
“…This hypothesis is further corroborated by the actual determinations of cGMP levels. Biochemical pathway for ␤ 3 -AR activation-mediated IAS smooth muscle relaxation is similar to that by neuronal nitric-oxide synthase and endothelial nitric-oxide synthase activation in the IAS (Rattan and Chakder, 1992;Chakder and Rattan, 1993;Banwait and Rattan, 2003). Data with ␤ 3 -AR activation in the IAS in view of its prolonged, selective, systemic effects-free effect (DiMarino et al, 2002;Banwait and Rattan, 2003) combined with the utilization of biochemical pathway common to nonadrenergic noncholinergic nerve stimulation are important from the standpoint of anorectal and other gastrointestinal motility disorders.…”
Section: Role Of Cgmp and Camp In ␤-Ar Activation 1117mentioning
confidence: 98%
“…They concluded that nitric oxide was an important substance involved in the relaxation of the smooth musculature of the anal canal. 7,9,10,24 To investigate the role of nitric oxide in sphincter hypotony of streptozotocin-induced diabetic rats, we used an antagonist of nitric oxide synthase: L-NAME. 25 We used L-NAME in the form of an enema in diabetic rats with sphincter hypotony 60 days after induction.…”
Section: Discussionmentioning
confidence: 99%
“…This suggestion is based on the following points: 1) direct inhibitory action of nitric oxide on the musculature, and 2) blockade of the inhibitory action of nonadrenergic and noncholinergic neurons through the use of inhibitors of the nitric oxide synthase (NOS). [8][9][10] The internal anal sphincter is a smooth muscle known to be under inhibitory control of nitric oxide. The use of Wistar rats as a model for experimental study is widely accepted, and its use for the study of diabetes and its complications is well documented.…”
mentioning
confidence: 99%